Resilience In High-level Injured Athletes Survey Of The Athletes Of The Senior National Karate And Vovianamviet Vo Dao Teams - Alloui , Tinhinane (sports creativity, 2025)
The practice of high level sport is considered as a factor of sports injuries and also as one of the most difficult stages to cross for an athlete, because it affects the psychological side as much as the physical side. However, athletes' reactions to these injuries are different, and this is linked to a dynamic process known as psychological resilience which allows the individual to show behavioral adjustment when faced with a difficult or traumatic situation. The present research retraces a survey carried out on (21) athletes exercising at the level of the national teams of Karate and vovianamviet vo dao and having suffered a physical injury. Also, the purpose of this study is to measure the level of resilence in these injured athletes, as well as to identify if there is a relationship between the level of resilence and gender factors as well as the duration of the injury.